2023
DOI: 10.1007/s10340-023-01622-8
|View full text |Cite
|
Sign up to set email alerts
|

Key role of environmental competence in successful use of entomopathogenic fungi in microbial pest control

Abstract: One of the main negative effects of climate change on biological pest control is alteration of relationships between insect pests and their natural enemies (both entomophagous and entomopathogenic). Indeed, environmental conditions can have multiple effects on pest control success when using entomopathogenic fungi (EPF), where conidial depletion, inactivation, and loss in virulence and infectivity can all occur. Appropriate mass production and formulation strategies for EPF can partially solve these problems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…A problem with successful pest control with many fungi is the level of susceptibility of the active organisms to external factors, such as fluctuations in temperature, humidity, and rainfall. Climate changes may significantly impact the relationship between fungi, insects, and crops and the interactions among them [ 196 ]. Furthermore, additional information needed for the eventual production of EFOPSZ as biopesticides would be the development of optimal methods for formulation and application.…”
Section: Discussionmentioning
confidence: 99%
“…A problem with successful pest control with many fungi is the level of susceptibility of the active organisms to external factors, such as fluctuations in temperature, humidity, and rainfall. Climate changes may significantly impact the relationship between fungi, insects, and crops and the interactions among them [ 196 ]. Furthermore, additional information needed for the eventual production of EFOPSZ as biopesticides would be the development of optimal methods for formulation and application.…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary factors impeding the longevity and efficacy of B. bassiana as a biocontrol agent against insect pests is its susceptibility to solar radiation, particularly UV-A and UV-B radiation. The exposure to UV-B radiation has been observed to significantly diminish the survival rate of B. bassiana conidia [82]. In light of this, research conducted in [83] has demonstrated the potential to enhance the spore durability of B. bassiana against UV radiation by incorporating natural substances known for their UV-protective properties, namely humic acid, sesame oil, and rapeseed oil.…”
Section: The Influence Of Various Adjuvants and Additives On The Effe...mentioning
confidence: 99%
“…12,13 The development of mycoinsecticides is a complex process concerning the selection of the fungal isolates, which must possess environmental competence. 14 Indeed, it has been suggested that during the initial infection process (germination and cuticle penetration), the fungus must be adapted to environmental factors such as temperature, humidity, solar radiation, microbial activity, and host physiology, which influence the persistence and efficacy of infective propagules. 7,15 C. capitata control with EPF has been investigated by targeting two nonprotected stages: pupae in soils and adults in epigeal areas.…”
Section: Introductionmentioning
confidence: 99%
“…7,27 The high variability in UV and particularly the UV-B radiation tolerance of different species, strains, and isolates of multiple entomopathogenic fungal species has been repeatedly reported, 19,21,[28][29][30] making the selection of strains with a higher UV-B resistance an option from which much is to be gained. 14 Since it usually takes around 24 h from the arrival of the fungal spore on the insect cuticle to invade the host body, 7 it is likely that the insect body does not protect the fungal conidia from irradiation if radiation takes place immediately after inoculation. However, since germination is negatively affected by UV radiation, 7 inoculation efficiency might be influenced by the irradiation, making it possible that inoculation with conidia right before radiation treatment will lead to less successful inoculation than the treatment in which the inoculation takes place after irradiation (and in which the conidia might have begun recovering).…”
Section: Introductionmentioning
confidence: 99%